Fertility of Male Sex-Sorted Semen in Khillar Cows Synchronized with Ovsynch Protocols - Diwakar, Barde Mayank; Ingawale, Maheshkumar Vitthalarao; Deshmukh, Shyam Ganesh; Hemednrakumar Pawshe, Chaitanya; Hajare, Sunil Wasudeo; Ingole, Ranjit Suresh; Awandkar, Sudhakar Pralhad (The Indian Journal of Animal Reproduction, 2026)
The study was conducted to evaluate the effect of male sex-sorted semen on pregnancy rate and sex ratio. Khillar cows (n=18) were synchronized by Ovsynch, Double PG Ovsynch and increasing dose of PG in Ovsynch synchronization protocols and inseminated with male sex-sorted semen. The higher pregnancy rate was observed in double PG Ovsynch synchronized cows than other two groups (50% vs 33.33%) which are non significant at (p